INDONESIA’S LOCAL CONTENT REPRESENTATION IN ASIAN GAMES 2018 MASCOT DESIGN - Saniscara, Pramesti (VCD, 2021)
Indonesia’s Local Content Representation in Asian Games’ 2018 Mascot Design. The Asian Games is a grand event in the field of sports which is held every four years and involves hundreds of athletes from all over Asia. Therefore, the Asian Games, in addition to being a sporting competition, are also allowing the host country to show their development and relevance in the international league. The Asian Games event is also a major concern of President Joko Widodo because of its potential to be the place for attracting investors and also promoting Indonesia’s tourism. One main focus towards this event is shown by using a graphic system and branding following design principles and harmonization with Indonesia’s local wisdom. The representation of Indonesian culture and representation of the motto of the 2018 Asian Games "Energy of Asia" must be embodied in the visual design of the 2018 Asian Games, including logo design, graphic systems, and mascot design Keyword: Asian Games 2018, vernacular design, mascot design, local content.